2005
DOI: 10.2746/0425164054406838
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in serum insulin‐like growth factor‐I, insulin‐like growth factor‐I binding protein‐3 and articular cartilage structure in Thoroughbred horses

Abstract: Summary Reasons for performing study: Structural changes in articular cartilage associated with the ageing process require definition for investigators performing developmental and age‐related studies, for which information is lacking. Objectives: To 1) determine the onset and end of puberty as defined by serum insulin like growth factor (IGF‐I) and IGF‐binding protein‐3 (IGFBP‐3) concentrations and 2) correlate articular‐epiphyseal cartilage complex structural changes with the onset and end of puberty. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
28
0
4

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 29 publications
5
28
0
4
Order By: Relevance
“…However, the progressive reduction in serum IGF-1 concentrations detected in Andalusian horses from one month of age to 10-14 years is not in agreement with the chronological evolution presented for other equine breeds. Fortier et al (2005) found high IGF-1 concentrations in Thoroughbred foals on Day 9 of age, with a decline to 7.5 months, increasing to a level comparable to neonatal concentrations and then again decreasing continuously to 15 months, after which time the concentrations remained relatively steady to 25 months of age. These authors found the peak concentrations at 8.5-10 months, whereas our peak concentrations were observed in the Andalusian foals aged 1-2 months.…”
Section: Influence Of Age On Serum Igf-1 Concentrations In Andalusianmentioning
confidence: 96%
See 3 more Smart Citations
“…However, the progressive reduction in serum IGF-1 concentrations detected in Andalusian horses from one month of age to 10-14 years is not in agreement with the chronological evolution presented for other equine breeds. Fortier et al (2005) found high IGF-1 concentrations in Thoroughbred foals on Day 9 of age, with a decline to 7.5 months, increasing to a level comparable to neonatal concentrations and then again decreasing continuously to 15 months, after which time the concentrations remained relatively steady to 25 months of age. These authors found the peak concentrations at 8.5-10 months, whereas our peak concentrations were observed in the Andalusian foals aged 1-2 months.…”
Section: Influence Of Age On Serum Igf-1 Concentrations In Andalusianmentioning
confidence: 96%
“…These authors did not find significant differences from three to eight years of age. In Thoroughbreds, Fortier et al (2005) found the highest IGF-1 concentrations at Day 9 of age, which steadily declined to Day 224 (approximately 7.5 months). After Day 224, serum IGF-1 concentrations increased to a level comparable to neonatal concentrations, and then again decreased continuously to Day 450 (approximately 15 months), after which time they remained relatively steady to Day 715 (approximately 31.8 months).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cross-reaction of the antibodies in these human kits with equine samples had been demonstrated previously, 28,29 or has been assumed on homology between equine and human protein structure. Glycosaminoglycans and DNA Analysis After lyophilizing for 24 h and recording dry weight, the tendon samples were papain digested.…”
Section: Growth Factor Quantificationmentioning
confidence: 99%